Administrative and legal status of the State Space Agency of Ukraine: historical and legal aspect - Юринець, Юлія Леонідівна; Свінціцька, Аліна Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The historical aspect of the administrative and legal regulation of the State Space Agency of Ukraine status. Consistently considered appropriate regulations, it turns out the shortcomings and contradictions of such regulation. In particular, it was found that the administrative and legal regulation in Ukraine in space activities initiated by Presidential Decree Ukraine from 29.02.1992 № 117 and at its development regulations approved by the Cabinet of Ministers of Ukraine of 06.01.1992 № 304. But these acts were not based on a solid legal basis, because at that time there was no specific law on the regulation of space activities, acts only in general outline administrative and legal status of the Agency and repeatedly subjected to changes or replacements to other acts. Instead State (until 09.12.2010 – National) Space Agency had permanent status of a central executive body. Administrative regulation of space activities characterized ridiculous and inconsistent regulation of this sphere, indicating the absence of the concept of sustainable development of the industry. Therefore, regulations that were made, were often subjective, contradictory, and sometimes the law. Proposed in the law of 16.10.2012 № 5461-VI division of powers between the CEB, which provides the state policy in the field of space activities and CEB, which implements the state policy in the sphere of space activity remained formal, because both groups continues to exercise authority only State Space agency of Ukraine. It is noted that describes administrative regulation reflects neglect of Ukrainian authorities to the development of space activities, which is reflected in its negative results and is also a reflection of the neglect of the Agency as the competent authority. The attention that the first question the need for space research to ensure the defense and security of the country is legally only in 2006. We give statistics that in 2013, Ukraine has experienced the development of space industry about 10 mln. UAH., While in Russia – $ 5 bln. Thus, the shortcomings in public sector management and reflected insufficient budgetary, financial and economic management, which doomed space industry in Ukraine hopeless lagging behind the world-class competition and the inability of aggressive neighbor to the east.